TOR-Dependent and -Independent Pathways Regulate Autophagy in Arabidopsis thaliana - Pu, Yunting; Luo, Xinjuan; Bassham, Diane C. (Frontiers in Plant Science, 2017)
Autophagy is a critical process for recycling of cytoplasmic materials during environmental stress, senescence and cellular remodeling. It is upregulated under a wide range of abiotic stress conditions and is important for stress tolerance. Autophagy is repressed by the protein kinase target of rapamycin (TOR), which is activated in response to nutrients and in turn upregulates cell growth and translation and inhibits autophagy. Down-regulation of TOR in Arabidopsis thaliana leads to constitutive autophagy and to decreased growth, but the relationship to stress conditions is unclear. Here we assess the extent to which TOR controls autophagy activation by abiotic stress. Overexpression of TOR inhibited autophagy activation by nutrient starvation, salt and osmotic stress, indicating that activation of autophagy under these conditions requires downregulation of TOR activity. In contrast, TOR overexpression had no effect on autophagy induced by oxidative stress or ER stress, suggesting that activation of autophagy by these conditions is independent of TOR function. The plant hormone auxin has been shown previously to up-regulate TOR activity. To confirm the existence of two pathways for activation of autophagy, dependent on the stress conditions, auxin was added exogenously to activate TOR, and the effect on autophagy under different conditions was assessed. Consistent with the effect of TOR overexpression, the addition of the auxin NAA inhibited autophagy during nutrient deficiency, salt and osmotic stress, but not during oxidative or ER stress. NAA treatment was unable to block autophagy induced by a TOR inhibitor or by a mutation in the TOR complex component RAPTOR1B, indicating that auxin is upstream of TOR in the regulation of autophagy. We conclude that repression of auxin-regulated TOR activity is required for autophagy activation in response to a subset of abiotic stress conditions.